Debating the Role of the Laity in the Hagiography of the Tenth-Century Anglo-Saxon Benedictine Reform - Riedel, Christopher (Revue bénédictine, 2017)
The leaders of the tenth-century English Benedictine reform movement, Dunstan, Æthelwold and Oswald, were each the subject of hagiographies in the 990s. These vitae demonstrate widely differing opinions about what qualities and interests were most important to their saintly subjects, and by extension to the reform movement as a whole, especially when it came to the importance of lay life and religion. Wulfstan Cantor, depicting the formidable Bishop Æthelwold, emphasizes that his saintly subject was a stern and zealous proponent of strict monasticism, but his keen interest in the laity can only really be understood when juxtaposed with the slightly later vitae of the other two reformers. In particular Byrhtferth of Ramsey's writings on Archbishop Oswald show that the last of the three hagiographers had little interest in the laity beyond their use in ritualized and formulaic depictions of the saint. Contrasting the very different portrayals of the interactions between the bishops and their lay congregations shows that the second generation of reformers, and perhaps even their saintly predecessors, had markedly differing attitudes towards their pastoral role in English society.